2015
DOI: 10.1038/ng.3222
|View full text |Cite|
|
Sign up to set email alerts
|

Analyses of allele-specific gene expression in highly divergent mouse crosses identifies pervasive allelic imbalance

Abstract: Complex human traits are influenced by variation in regulatory DNA through mechanisms that are not fully understood. Since regulatory elements are conserved between humans and mice, a thorough annotation of cis regulatory variants in mice could aid in this process. Here we provide a detailed portrait of mouse gene expression across multiple tissues in a three-way diallel. Greater than 80% of mouse genes have cis regulatory variation. These effects influence complex traits and usually extend to the human orthol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
234
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(256 citation statements)
references
References 58 publications
19
234
3
Order By: Relevance
“…Allelic imbalance, preferential expression of an allele in diploid organisms, is a fairly common phenomenon. [17][18][19] Thus, the risk allele seems to show greater expression despite the fact that no coherent genotypic impact on whole blood expression level (CC>CT>TT) was evident. Similarly, previous studies have failed to identify rs11556924 as an expression quantitative locus for ZC3HC1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Allelic imbalance, preferential expression of an allele in diploid organisms, is a fairly common phenomenon. [17][18][19] Thus, the risk allele seems to show greater expression despite the fact that no coherent genotypic impact on whole blood expression level (CC>CT>TT) was evident. Similarly, previous studies have failed to identify rs11556924 as an expression quantitative locus for ZC3HC1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong consensus emerging from the analyses of a variety of model organisms: in yeast (Kvitek et al 2008;Artieri and Fraser 2014), fly (Wang et al 2008;Coolon et al 2014Coolon et al , 2015Graze et al 2014), and mouse (Goncalves et al 2012;Crowley et al 2015;Pinter et al 2015) that cis-and trans-effects are compensatory. In intraspecific D. melanogaster F 1 's, compensatory interactions were observed in 79% of cases, and in interspecific D. simulans/D.…”
Section: Discussionmentioning
confidence: 99%
“…They have been implicated in human disease phenotypes such as cancer and are an important component of variation in Drosophila, as well as yeast, plants, animals, and humans (Mendell and Dietz 2001;Brem et al 2002;Cowles et al 2002;Yan et al 2002;Wittkopp et al 2004Wittkopp et al , 2006Wittkopp et al , 2008bSpringer and Stupar 2007;Hutter et al 2008;Smith and Kruglyak 2008;Tirosh et al 2009;Emerson et al 2010;McManus et al 2010;Crowley et al 2015). In Drosophila, variation in gene expression is heritable (Wayne et al , 2007 and evidence for both cis-and transregulatory polymorphisms is widespread (Wittkopp et al 2004(Wittkopp et al , 2008bHughes et al 2006;Genissel et al 2008;Wang et al 2008;Graze et al 2009Graze et al , 2012Graze et al , 2014 and evidence for cis-by trans-interactions has been reported (Wittkopp et al 2004(Wittkopp et al , 2008bWang et al 2008;Graze et al 2014).…”
mentioning
confidence: 99%
“…Genotype-associated allelic imbalances, regulated by expression quantitative trait loci (eQTLs) in cis, are acknowledged to be a widespread source of phenotypic variation in humans (Ge et al 2009) and mouse (Crowley et al 2015). Monoallelic expression can also be epigenetically controlled in a parent-of-origin specific manner, as exemplified by genomic imprinting (Reik and Walter 2001), a relatively rare phenomenon affecting approximately 100 genes in human and 120-180 genes in mouse (Babak et al 2015;Baran et al 2015;Crowley et al 2015). Monoallelic gene expression can also be random, whereby a cell stochastically expresses a single allele.…”
Section: Introductionmentioning
confidence: 99%